2015
DOI: 10.3899/jrheum.140949
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the IFI16 Gene Affecting the Levels of Expression of mRNA Are Associated with Susceptibility to Behçet Disease

Abstract: Our findings suggest association of IFI16, a cytosolic sensor of dsDNA and mediator of the AIM2 inflammasome-dependent pathway, in susceptibility to BD. Differences genetically determined in the levels of this molecule could be the cause of this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…These results are in support of the current data and the concept that changes in the innate immune functions can alter the host response and facilitate development of diseases. A recent study found that IFI16 rs6940 (also identified in this study) and AIM2 rs855873 (also upstream of AIM2 ) were associated with increased susceptibility to Behçet disease, a systemic immune‐mediated disease characterized by vasculitis and recurrent mucosal ulcerations 41 . The study shows rs6940 decreases expression of anti‐inflammatory IFI16 and increases susceptibility to an immune‐mediated disease 41 .…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…These results are in support of the current data and the concept that changes in the innate immune functions can alter the host response and facilitate development of diseases. A recent study found that IFI16 rs6940 (also identified in this study) and AIM2 rs855873 (also upstream of AIM2 ) were associated with increased susceptibility to Behçet disease, a systemic immune‐mediated disease characterized by vasculitis and recurrent mucosal ulcerations 41 . The study shows rs6940 decreases expression of anti‐inflammatory IFI16 and increases susceptibility to an immune‐mediated disease 41 .…”
Section: Discussionsupporting
confidence: 71%
“…A recent study found that IFI16 rs6940 (also identified in this study) and AIM2 rs855873 (also upstream of AIM2 ) were associated with increased susceptibility to Behçet disease, a systemic immune‐mediated disease characterized by vasculitis and recurrent mucosal ulcerations 41 . The study shows rs6940 decreases expression of anti‐inflammatory IFI16 and increases susceptibility to an immune‐mediated disease 41 . The fact that Behçet is associated with epithelial ulceration and the present results show associations of these SNPs with BOP suggests that these variants may impair innate immune responses that maintain epithelial integrity at mucosal surfaces.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In one study conducted with 371 patients with BD, an association was found between the disease and the IFI16 single nucleotide polymorphism, a mediator of the AIM2-inflammasome pathway. 64 Four mutations of the NLRP3/cryopyrin gene were identified in a study conducted with 50 cases of BD. 65 However, another study was unable to demonstrate a greater activation of caspase-1 through the inflammasome pathway in dendritic cells and neutrophils of sick patients, as compared to the controls.…”
Section: Dermatological Diseases Associated With Inflammasomesmentioning
confidence: 99%